2008
DOI: 10.1080/19401490701868299
|View full text |Cite
|
Sign up to set email alerts
|

Efficient calculation of daylight coefficients for rooms with dissimilar complex fenestration systems

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Orientation of the living space with respect to light source, geometry of the living space, optical properties of interior surfaces of the living space, obstructions outside the room, and optical characteristics of glazing play a major role in harnessing daylight [27]. The daylight coefficient for complex fenestration has been examined, and it was concluded that the daylight coefficient does not depend on luminance distribution in the sky [28,29]. The illuminance level from natural light has been estimated by Rosa et al [30] for overcast sky conditions.…”
Section: History Of Daylightingmentioning
confidence: 99%
“…Orientation of the living space with respect to light source, geometry of the living space, optical properties of interior surfaces of the living space, obstructions outside the room, and optical characteristics of glazing play a major role in harnessing daylight [27]. The daylight coefficient for complex fenestration has been examined, and it was concluded that the daylight coefficient does not depend on luminance distribution in the sky [28,29]. The illuminance level from natural light has been estimated by Rosa et al [30] for overcast sky conditions.…”
Section: History Of Daylightingmentioning
confidence: 99%
“…Standardized DC models for dynamic simulations have been proposed and validated (Bourgeois, Reinhart, and Ward 2008;Laouadi, Reinhart, and Bourgeois 2008). The DCs are accumulated and scaled with luminance distributions from a time-series in a postprocess, resulting in the predicted illuminance at the sensor points.…”
Section: Daylight Coefficientsmentioning
confidence: 99%
“…Laouadi et al [21] had reported that the daylight factor of building depends upon position of light source with respect to the room orientation, the room geometry, the optical characteristics of the room indoor surfaces, any outdoor obstructions and the optical behaviour (transmission, reflection and light scattering) of the fenestration system through which light is admitted into the room space. Daylight coefficient is independent of sky luminance distribution as reported by Tregenza and Waters [22].…”
Section: Introductionmentioning
confidence: 99%